2022
DOI: 10.21831/jipi.v7i2.41172
|View full text |Cite
|
Sign up to set email alerts
|

Science learning development for the deaf: A digital literacy based learning design

Abstract: Digital literacy-based learning is needed for deaf students in understanding style and motion material. Application assisted learning in the form of e-books is specially designed for the deaf with an attractive design, which is accompanied by visual animations of the application of style and motion in everyday life. Thus, the understanding of the material obtained is not only through text.But animations of every kind of style and examples. The pupose of this research is to develop and determine the feasibility… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Products that have been assessed by panelists and meet the requirements can be used in limited trials (Hardiyansyah et al, 2019;Kartini et al, 2019). A worthy product certainly meets the specified assessment standards (Purwasih et al, 2022;Rosnawati & Sunaryati, 2021). Products that have been declared suitable for use are then used in learning on a limited basis.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Products that have been assessed by panelists and meet the requirements can be used in limited trials (Hardiyansyah et al, 2019;Kartini et al, 2019). A worthy product certainly meets the specified assessment standards (Purwasih et al, 2022;Rosnawati & Sunaryati, 2021). Products that have been declared suitable for use are then used in learning on a limited basis.…”
Section: Resultsmentioning
confidence: 99%
“…It is hoped that the encyclopedia will add to the body of knowledge that is more real and contextual. contextuality in a learning resource can be taken from a phenomenon in everyday life (Purwasih et al, 2022). The uniqueness of a phenomenon in daily life that a region has and increases welfare is usually known as local potential (Purwasih et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a consequence of this situation, several university science programs offer compulsory modules for first-year students, teaching them RS and DLS (Curtis et al, 2017). It is recently found that students' digital literacy positively affects learning outcomes in science subjects (Akhyar et al, 2021;Latip et al, 2022) Despite the importance of DLS and RS for academic success (Briggs et al, 2012;Hurwitz and Schmitt, 2020;Oostdam et al, 2007), only a few scientific studies have addressed the development of these skills in secondary education and the way this affects the ensuing transition to science undergraduate education. Most studies in this field have focused on students' characteristics (Maddens et al, 2021;Smith and White, 2015), general transition factors (Leese, 2010), teaching and testing approaches (Mumba et al, 2002) or a mismatch of STEM syllabi (De Meester et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Learning science material about motion and style using a website is a form of implementing digital literacy-based learning. In learning science, students will build character and apply the knowledge, attitudes and skills that students get through learning experiences using science and technology (R. D. Kurniawati et al, 2022;W. M. Sari et al, 2022;Wilujeng et al, 2020).…”
Section: Introductionmentioning
confidence: 99%